Red Hill - McGuire, Jamie (ATRIA PAPERBACK, 2013)
"When the world ends, can love survive? For Scarlet, raising her two daughters alone makes fighting for tomorrow an everyday battle. Nathan has a wife, but can't remember what it's like to be in love; only his young daughter Zoe makes coming home worthwhile. Miranda's biggest concern is whether her new VW Bug is big enough to carry her sister and their boyfriends on a weekend escape from college finals. When reports of a widespread, deadly 'outbreak' begin to surface, these ordinary people face extraordinary circumstances and suddenly their fates are intertwined"